2017
DOI: 10.1084/jem.20171052
|View full text |Cite|
|
Sign up to set email alerts
|

Prostate-specific membrane antigen cleavage of vitamin B9 stimulates oncogenic signaling through metabotropic glutamate receptors

Abstract: Kaittanis et al. show that the processing of glutamated folates by prostate-specific membrane antigen induces the activation of metabotropic glutamate receptors and initiation of PI3K–Akt signaling in prostate cancer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

7
136
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 137 publications
(144 citation statements)
references
References 46 publications
(62 reference statements)
7
136
1
Order By: Relevance
“…16 Recent work suggested that the enzymatic function of PSMA is cleaving glutamate, thereby activating the glutamate driven phosphoinositide 3-kinase and subsequently the mammalian target of rapamycin (mTOR) pathway. 17 PSMA expression is known to be upregulated up to a thousand-fold higher in prostate cancer compared to normal prostate tissue. Thus, PSMA represents a potential target for imaging and therapy of prostate cancer.…”
Section: Discussionmentioning
confidence: 99%
“…16 Recent work suggested that the enzymatic function of PSMA is cleaving glutamate, thereby activating the glutamate driven phosphoinositide 3-kinase and subsequently the mammalian target of rapamycin (mTOR) pathway. 17 PSMA expression is known to be upregulated up to a thousand-fold higher in prostate cancer compared to normal prostate tissue. Thus, PSMA represents a potential target for imaging and therapy of prostate cancer.…”
Section: Discussionmentioning
confidence: 99%
“…The addition of novel imaging or biomarkers may increase the detection of PCa missed by mpMRI. Prostate-specific membrane antigen (PSMA) is a cell surface transmembrane glycoprotein expressed on the cell surface by the majority of PCa cells, with its expression increasing in higher-grade malignancy [11,12]. Recently, PSMA-positron-emission tomography (PET)/CT imaging has become increasingly used in the detection of metastatic disease, especially in patients with biochemical recurrence after local treatment [13][14][15][16][17][18][19][20][21].…”
Section: Introductionmentioning
confidence: 99%
“…Its capacity to release glutamate form N-acetyl-l-aspartyl-glutamate (NAAG) is being explored for its therapeutic potential for brain ischemic injury and several neurodegenerative disorders. Kaittanis et al (2018) investigate the folate hydrolase activity of PSMA in prostate cancer, its biological function (uncharted thus far), and, most importantly, its potential as a therapeutic target (see figure). Kaittanis et al (2018) observe a strong positive correlation between PSMA expression, disease aggressiveness, and phosphorylation of the AKT target in prostate tumor tissue from patients with localized disease.…”
mentioning
confidence: 99%
“…Kaittanis et al (2018) investigate the folate hydrolase activity of PSMA in prostate cancer, its biological function (uncharted thus far), and, most importantly, its potential as a therapeutic target (see figure). Kaittanis et al (2018) observe a strong positive correlation between PSMA expression, disease aggressiveness, and phosphorylation of the AKT target in prostate tumor tissue from patients with localized disease. Based on this evidence, they hypothesized a significant role for PSMA in modulating signaling pathways implicated in the pathogenesis of prostate cancer, specifically the PI3K-AKT-mTOR pathway.…”
mentioning
confidence: 99%
See 1 more Smart Citation